A History of Amba Prisons and Imprisonment in Gojjam (1382 –1941) - Sishagn, Shumet; Tariku, Ayele; Gebeyehu, Temesgen (Ethiopian Journal of Social Sciences, 2023)
The main objective of this study is to reconstruct the history of Amba prisons and imprisonment in Ethiopia from the 14th to 20th century. The period refers to the establishment of Jäbäla Amba as a modern prison in 1941. The study employed qualitative methodology with which primary and secondary sources were exhaustively exploited. The study interviewed notable elders who had information about the prison and imprisonment. Besides, the study made practical observations and photographed the Amba prisons and caves. The information was cross-checked with other sources such as travellers’ accounts, manuscripts and chronicles. The research identified many prison Ambas in Gojjam that served as prisons where offenses were punished by imprisonment from 14th to 20th century.Jäbäla, Quami Çäriq, Lib Gaša, Wamit and Särka were some of them. Emperor Dawit (r. 1382–1413) built Jäbäla Hobalit Maryam Church on the Jäbäla Mountain, making Jäbäla Amba one of the prisons in Gojjam's history.